SAJEN SAM-SAM: MEDIA PERINTISAN DESA MANDIRI MELALUI PENINGKATAN JIWA WIRAUSAHA, KEMANDIRIAN, DAN DAYA KREATIVITAS MASYARAKAT DESA TOTOSAN KECAMATAN BATANG-BATANG KABUPATEN SUMENEP DALAM MENGOLAH BUAH DAN NIRA SIWALAN MENJADI JAJANAN KHAS PULAU MADURA - F., Febriyanto; Fawaid, Ach.; R., Ruka’iya; Ristiani, Yuli (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Most of the palm trees grow in Totosan village, Trunks district, Kabupaten Sumenep, which covers 80 % of the total area. During this the community sell only palm in fresh form. When being analyzed, these economic activities are not effective and efficient. Community service programs through innovation and the sap of palm fruit processing is done to enhance the entrepreneurial spirit, independence and community kreativifas in processing power potential in the vicinity into Sam - Sam Sajen products as specific snacks of the island of Madura in order to increase incomes. PKM - M activities conducted from 17 February to 30 June 2013 and is divided into 4 main activities of observation, the introduction Sajen Sam - Sam, a variety of training and evaluation. Society has learned that Sam - Sam Sajen products to increase the added value of palm, both in terms of taste, aroma, color, price (2-3 fold increase profits) and product shelf life (4-5 months). The high business prospects can be attributed to the entrepreneurial spirit, independence and creativity of the people in the process surrounding the potential of becoming Sajen Sam - Sam marked with the scale greater community that are 90 cup jelly, jam bottles 20, 50 cup candied wet and dry and 45 cup nata per-day as well as the increasing number of people who started the business processing into products Sajen Sam - Sam, but from raw material bananas. Positive responses from the various elements of society in various areas of Madura by organoleptic test results, levels of increasing demand and support from the relevant Department to be an indicator that the processed products Sajen Sam - Sam accepted as typical products of the island of Madura snacks. Government and the general public need to socialize and develop the processing technology of fruit and palm sap into Sam - Sam Sajen products, mainly raw materials from a variety of other fruit into Sajen Sam - Sam is optimal to increase the value -added products, entrepreneurial spirit, independence, and creativity the local community.